OPTIMIZATION OF THE TRANSPORT AND TECHNOLOGICAL SCHEME OF TRANSPORTATION OF AGRICULTURAL PRODUCTS IN THE SPECIAL CONDITIONS OF UKRAINE - Lesnikova, I. Yu.; Khalipova, N. V.; Kuzmenko, A. I.; Zhyr, S. I.; Shapovalov, A. V. (Systems and Technologies, 2023)
The article is devoted to improvement of transport and technological scheme of transportation of agricultural products under martial law. The optimal route for transportation has been determined. Calculated indicators of the cost of transportation of agricultural products. Ukraine is one of the largest producers of grain crops, among which the main place is occupied by wheat, as well as millet, sorghum, corn, rye, oats, barley and rice, which are used in the food industry, livestock and livestock waste. During the war, this issue became perhaps the most important because of the threat of a shortage of grain stocks in most countries that purchased it from our country every year The relevance of the bottom article is due to the fact that in the conditions of war, grain transportation by road takes the first position in the freight market in terms of volume on a par with rail, because these are the only modes of transport that can function during the war in Ukraine. Alternative modes of transport have lost the ability to work fully or are not available at all. Airspace is completely closed, most of the ports are under temporary occupation or are unable to work fully because their infrastructure is partially destroyed. Consequently, road transportation is becoming one of the main ways of exporting grain crops. The article is aimed at optimizing ways to improve the efficiency of management of the process of cargo transportation and organization of cargo delivery (on the example of grain crops) under martial law. The criterion of minimization of total transport costs and the optimal plan of transportation of wheat from suppliers to enterprises and port are determined. It is found out which part of the total transport costs falls on the first stage of transportation (from suppliers to distribution points), and which on the second (from distribution points to final points). As a result of the use of Internet resources “Trypillya” and “DeGruz” summary data on the cost of transported cargo from suppliers to intermediate points and from intermediate points to consumers. According to the results, an optimized transportation plan was obtained, a comparison of transportation costs before and after optimization was made, the cost of which significantly decreased compared to the previous one, namely by 9%, which is a significant result during the war.